Racial and ethnic disparities in paranasal sinus malignancies. Issue 11 (6th June 2021) - Sharma, Rahul K.; Schlosser, Rodney J.; Beswick, Daniel M.; Suh, Jeffrey D.; Overdevest, Jonathan; McKinney, Kibwei; Gudis, David A.
Abstract: Background: Racial and ethnic disparities in cancer outcomes have been demonstrated for several different malignancies. In this study we aimed to quantify disease‐specific survival (DSS) and the 5‐year conditional disease‐specific survival (CDSS, the change in life expectancy with increasing survivorship) for paranasal sinus cancer by race and ethnicity. Methods: Patients with sinus cancer between 1973 and 2015 were extracted from the Surveillance, Epidemiology, End Results (SEER) registry. Kaplan‐Meier analysis for DSS was stratified by race and ethnicity. Cox regression models of DSS were generated controlling for stage, age, race, and ethnicity. CDSS was calculated using Cox models. Logistic regression was conducted to identify risk factors for younger age at diagnosis, late‐stage at diagnosis, and likelihood of receiving surgical intervention when recommended. Results: The analysis included a total of 5202 patients. DSS was significantly different when stratified by race ( p  < 0.01). Compared with White patients, Black patients (hazard ratio [HR], 1.29; 95% confidence interval [CI], 1.13‐1.45; p  < 0.001) and American Indian/Alaskan Natives (HR, 1.94; 95% CI, 1.37‐2.74, p  < 0.001) exhibited increased mortality when controlling for other factors. Black patients had worse CDSS for regional and distant staged cancer compared with other races; American Indian/Alaskan Native patients had worse CDSS for cancers of all stages. Hispanic patients were more likely to present with advanced disease (odds ratio [OR], 1.47; 95% CI, 1.07‐2.07; p  = 0.020). American Indian/Alaskan Native patients were less likely than White patients to receive surgical intervention when recommended (OR, 0.42; 95% CI, 0.21‐0.04; p  = 0.024). Nonwhite patients were more likely to be diagnosed at a younger age. Variations in racial and ethnic disparities were observed over time. Conclusion: Race and ethnicity significantly impact paranasal sinus cancer outcome metrics. Disparities in outcomes are likely multifactorial.